1993
DOI: 10.1007/bf00024258
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aminooxyacetic acid and cytokinin combinations on carnation flower longevity

Abstract: A simplified method, which utilizes a 50% senescence value (Sse) for the measurement of longevity, in cut carnation flowers is used to compare flower longevity. A pulsed treatment using a combination of aminooxyacetic acid (AOA), kinetin and Triton X-100 enhanced flower vase-life relative to a water control. The mixture, however, did not exhibit synergistic effects when Sse values of the individual compounds were compared. A single AOA pulse treatment was as effective as the mixture. These findings held true f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
1
3
0
1
Order By: Relevance
“…This result concurs with those of Bossè and van Staden (1989) and Bichara and van Staden (1993), who found that vase solution-supplied BA did not affect carnation flower longevity. However, these same workers determined that vase solution-supplied dihydrozeatin could delay senescence in carnation.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…This result concurs with those of Bossè and van Staden (1989) and Bichara and van Staden (1993), who found that vase solution-supplied BA did not affect carnation flower longevity. However, these same workers determined that vase solution-supplied dihydrozeatin could delay senescence in carnation.…”
Section: Discussionsupporting
confidence: 92%
“…As BA applied as dips delayed senescence in G. 'Sylvia', it would be of interest to determine whether carnation senescence could also be altered by BA dip-treatment (cf. Bossè and van Staden 1989;Bichara and van Staden 1993). Mor et al (1983) recorded delayed senescence when carnation petals were floated on BA solutions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O ácido aminooxiacético é inibidor da sintase do ACC, enzima responsável pela conversão do composto S-adenosil-L-metionina (SAM) para 1-aminociclopropano-1-ácido carboxílico (Altvorst & Bovy, 1995). O tratamento com ácido aminooxiacético é eficiente em reduzir a respiração, produção de etileno e elevar a vida em vaso das flores de orquídeas do gê-nero Phalaenopsis (Woltering, 1987;Porat et al, 1995) e Cymbidium (Goh et al, 1985) e de Dianthus (Bichara & Staden, 1993;Uda et al, 1997). Em algumas variedades de Rosa hybrida, a utilização de solução de vaso com sacarose a 5% mais 0,5 mM de ácido aminooxiacético aumenta significativamente a vida em vaso (Ketsa & Narkbua, 2001).…”
Section: Introductionunclassified
“…Kirchner et al (1993) recently described the effects of new dérivâtes of AOA on the inhibition of ethylene biosynthesis. The activity of ACC oxidase can be blocked by Co 2+ (Satoh and Esashi, 1983), Triton X-100 (Harkema et al, 1987;Bichara and Van Staden, 1993), σ-aminoisobutyic acid (AIB) (Satoh and Esashi, 1983) and allocoronamic acid dérivâtes (Toshima et al, 1993). Since inhibitors of ACC synthase and ACC oxidase only prevent ethylene biosynthesis, they offer little protection in ethylene-polluted environments.…”
Section: Inhibitors Of Acc Synthase and Acc Oxidasementioning
confidence: 99%